SECON: ANALYSIS OF THE MODEL FOR IPHONE USER BRAND LOYALTY IMPROVEMENT IN SEMARANG CITY - Arsanda, Tiara Daffa; Putra, Febrianur Ibnu Fitroh Sukono; Lestari, Selvia Puji (Lembaga Pengembangan Kinerja Dosen, 2021)
This study aims to produce a Brand Loyalty Improvement Model Based on Brand Satisfaction and Self Congruity for iPhone Users in Semarang City. The population in this study were iPhone users in the city of Semarang. The sampling technique was non-probability sampling, while the sample was set at 125 people. Data collection techniques used are interviews (Interview) and a list of questions (Questionaire). The data analysis method used in this research is the Structural Equation Model method. The results showed that Actual Self affected Brand Satisfaction, Actual Self had an effect on Brand Loyalty, Ideal Self had an effect on Brand Satisfaction, Ideal Self affected Brand Loyalty, Brand Satisfaction affected Brand Loyalty. Brand Satisfaction can positively mediate the influence of Actual Self on Brand Loyalty, and Brand Satisfaction can positively mediate the influence of Ideal Self on Brand Loyalty.